Microfluidic Cooling System in High-Power Bare Chip Modules Based on New Process Technology - Li Lidan; Qian Zifu; Zhang Qingjun; Liu Yajun; Li Zhi; Li Peng (Zhileng xuebao)
A closed-loop integrated microfluidic cooling system was designed to mitigate the heat dissipation problem in a high-power bare chip. The heat dissipation capabilities of a microchannel manufactured in the cavity and an unmanufactured cavity were compared. Moreover, the heat dissipation capabilities of a straight microchannel cavity and a cross-linked microchannel cavity were compared. The results show that the heat dissipation capability of the bare chip with a microchannel cavity was better than that of the unmanufactured one, and the heat dissipation capability of the bare chip with a cross-linked microchannel cavity was better than that of a straight microchannel one. The bare chip was welded to the diamond heat sink by eutectic soldering, and the diamond heat sink was welded to the power module cavity by eutectic soldering, which reduced the thermal resistance between the power module cavity and the bare chip by a factor of 280–360 from traditional methods. Experiments and simulation calculations of the heat dissipation ability of the microfluidic cooling system were performed. The experimental and simulation results are in notable agreement, and the maximum deviation was only 7.16%. The results show that the microfluidic cooling system has a strong heat dissipation ability that can handle a 320 W/cm2 heat flux on the bare chip at 70 °C ambient temperature.